Stable RuIr Nanoalloy Catalyst for Levulinic Acid Hydrogenation Reaction - Jingru Wang; Xianshu Dong; Yuping Fan; Yingyong Wang; Xiangyun Guo (Molecules)
Hydrogenation of levulinic acid (LA) represents a significant approach for producing the high-value biomass-based platform compound γ-valerolactone (GVL). In this study, an efficient RuIr alloy bimetallic catalyst supported on SiC was synthesized and applied for the aqueous hydrogenation of LA into GVL under mild conditions. The RuIr/SiC catalyst exhibited high LA conversion and GVL selectivity (both > 99%) in water at 0.2 MPa H2 pressure and 25 °C. The excellent performance is attributed to the synergistic interaction between Ru and Ir nanoparticles on the semiconducting SiC support. Furthermore, the catalytic activity of the RuIr/SiC alloy remained basically unchanged after five cycles, confirming the high stability of the bimetallic alloy catalyst.